PENGGUNAAN BEBERAPA TAKARAN DAN JENIS MULSA GULMA SERTA PENGARUHNYA TERHADAP EFISIENSI PENGENDALIAN GULMA DAN HASIL KEDELAI - Triyono, Kharis - (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2011)
PENGGUNAAN BEBERAPA TAKARAN DAN JENIS MULSA GULMA SERTA PENGARUHNYA TERHADAP EFISIENSI PENGENDALIAN GULMA DAN HASIL KEDELAI THE USING OF SOME DOSAGES AND KINDS OF WEED MULCH AND ITâ€™S EFFECTS ON WEED CONTROL EFFICIENCY AND SOYBEAN YIELD Â Kharis Triyono Â Abstract A research has been conducted in Tegal Gedhe village, Karanganyar Regency Central Java started June 2010 until September 2010. The object of the research is to observe the using of some dosages and kinds of weed mulch on weed control efficiency and soybean yield. Randomized Completely Block Design was used by factorial with three replication . Dosages factors were : 7 , 14, and 21 ton ha-1. While kinds of weed mulch were : cogon grass, water hyacinth and in situ. The result showed that dosages and kinds of weed mulch individually , effect weed control efficiency at 21 and 42 DAP, number pod per plant, number seed per plant and seed dry yield. There were interaction between dosage and kinds of weed mulch on number seed per plant and seed dry yield. Dosages of weed mulch of cogon grass at 21 ton ha-1 could increase seed dry yield to 56 percent. Keywords : Weed mulch, cogon grass, water hyacinth, soybean